A Clustering Metbod Based on tbe Tbresbold in Wireless Heterogeneous Network - Dongsheng Han; Shasha Ding; Ping Yu (Dianxin kexue)
The base station clustering problems in wireless heterogeneous network to suppress the inter cell interference were studied.A clustering method based on the threshold,which can improve the system performance,was proposed.The method maximizes the transmission rate for the target under the heterogeneous network scenarios,then selecting the base stations meeting the threshold value to collaborate,at the same time considering the user belonging-base station's signal intensity and the no-belongings' interference.The receiver transmission rate in different clustering methods was analyzed.The simulation results show that the proposed method is better than the existing methods in the system transmission rate.